Trend Tema Penulisan Skripsi Ilmu Sejarah 2006-2020 ( Studi Historiografi ) - Dian Safitri; Hendra Naldi (Jurusan Sejarah FIS UNP, 2021)
This study aims to determine the trend in choosing the theme of History Science thesis in 2006-2020 and also to explain the reason why History Student from 2006-2020 chose the title of History Science Theme. In writing this research using the method of conten analysis (Conten Ananlysis) which consists of the following steps data collection, content analysis, and writing (Description). Based on the results of the research, it was found that in 2006-2020 the tendency of students to choose in the field of historical Science was the Biography theme, after that students tended to take the Socio-Ekonomic, Ekonomic, Institutional and Social Themes compared to other themes, in addition, the Tedency of choosing this theme is closely related to the motivation of the students themselves, in addition to the motivational factors of the students themselved, the selection of this them field is also external factors that couse students to tend to take the theme, in cluding the studen supervisors who choose the theme because they now that with the title theme they wiil get the lecturer, because if the supervisor guides regularly and quickly, our thesis will be ready quickly.